The creative cycle and the growth of psychological science - Fiedler, Klaus (Perspectives on psychological science, 2018)
Scientific progress relies on the dialectics of loosening and tightening processes. Although most gripping accomplishments in psychological science testify to the critical role of creative and inno...
Gesehen am 15.04.2020